Graphene-silicon Schottky devices for operation in aqueous environments: Device performance and sensing application. (July 2022) - Angizi, Shayan; Selvaganapathy, P. Ravi; Kruse, Peter
Abstract: Graphene/silicon Schottky diodes have recently been of heightened interest due to their high sensitivity towards surface chemical modifications. Here we demonstrate the operation of a graphene/n-type silicon Schottky junction in aqueous media, quantifying the impacts of the ionic strength, oxidation-reduction potential, and pH of an aqueous solution on diode characteristics. The roles of the electrical double layer and the surface functional groups of graphene in determining the graphene/silicon junction response to changes in the aqueous environment were investigated. The application of this diode sensor design was demonstrated in an aqueous environment by the introduction of functional groups to the graphene surface via non-covalent functionalization (here with 1-aminopyrene). Free chlorine - a common disinfectant for drinking water - is used to illustrate the sensing capabilities of this new platform, demonstrating up to 80% change in series resistance (4% change in Schottky barrier height) of the functionalized device upon exposure to 1 ppm free chlorine, while the unfunctionalized device only shows a 17% response. The results achieved in this study will open up new opportunities for highly sensitive detection of (bio)analytes using graphene/silicon diode devices in aqueous environments, beyond their conventional gas sensing applications. Graphical abstract: Image 1